Impact of Corona Virus On Total Share In All Company Sectors In Indonesia Stock Exchange - An Suci Azzahra; Ayu Wirdha Ningsih (International Journal of Science, Technology & Management, 2021)
The purpose of this study is to analyze the impact of the corona virus on total shares in all company sectors on the Indonesia Stock Exchange. This study examines whether there are differences in total shares before and after Covid-19 was announced in Indonesia. The data consists of total shares on January 31, 2020 (30 days before the announcement of COVID-19) and total shares on March 31, 2020 (30 days after the announcement of COVID-19) for all company sectors on the IDX. The method used is descriptive quantitative. The analysis technique in this study consists of descriptive statistics and hypothesis testing using the nonparametric MANOVA method on the STATCAL software. The results showed that there was a significant difference in the total shares before and after the announcement of the first case of covid-19 in Indonesia in sectors 1, 3, 4, 6, 7, 8 and 9, indicated by a significant value per company sector in all sectors < 0, 05, while for sectors 2 and 5 there is no significant difference. The value of the permutation test p-value is 0.01, i.e. < 0.05 level of significance, it can be concluded that overall, there is a significant difference in total shares 30 days before and after the announcement of COVID-19.